Analysis of Science Laboratory Management to Support Science Learning: A Systematic Review - Setiya Rini, Endah Febri; Bramastia, Bramastia; Aditia, Kevin; Fitriani, Fitriani; Siswanto, Predy (Integrated Science Education Journal, 2024)
Purpose of the study: An Merdeka curriculum requires students to be able to acquire scientific attitudes and process skills in science learning. Laboratory management is very important in supporting science learning. This research aims to analyze the management of science laboratories to support science learning. Methodology: This type of research is qualitative research using a systematic literature review method. The population in this study was 60 articles originating from Google Scholar with publications from 2018 to 2023 which were then filtered again and a sample of 18 articles was obtained. The data analysis technique uses the matrix method. Main Findings: Based on the results of a systematic literature review analysis, it is known that laboratory management in several schools has factors inhibiting laboratory management, such as the unavailability of laboratory personnel and technicians, multifunctional laboratory space, allocation of time for laboratory use, and lack of infrastructure in science laboratories. The conclusion in this research is that based on a review of literature studies, it is known that in the management of science laboratories in junior high schools, in some literature there are still inhibiting factors in its management. Novelty/Originality of this study: The novelty in this research is the existence of a literature study which discusses the management of science laboratories in supporting science learning.